Prioritizing Infection Prevention and Control Activities for SARS-CoV-2 (COVID-19): A Multi-Criteria Decision-Analysis Method - Sarwar A; Imran M (Dove Medical Press, 2021)
Adnan Sarwar, Muhammad Imran Department of Economics and Business Management, University of Veterinary and Animal Sciences, Lahore, PakistanCorrespondence: Adnan SarwarDepartment of Economics and Business Management, University of Veterinary and Animal Sciences, Lahore, PakistanTel +92 3007699710Email adnansarwar@live.comPurpose: The outbreak of COVID-19 in China has spread to the whole world within a short period. The spread of COVID-19 has caused innumerable economic and social losses. The coronavirus spread directly from individual to individual. WHO and other governing bodies made guidelines and remedial activities to minimize the spread of COVID-19. This study aims to analyze and prioritize infection prevention and control activities for SARS-CoV-2.Methods: An analytical study was conducted between medical representatives and scientists to check the impact of these precautionary measures (social distancing, shaking hands and hugging peoples, unnecessary touching things, hygiene, and sharing personal items) on COVID-19. The Analytical Hierarchical Process (AHP) method has been utilized to evaluate and prioritize the preventive measures of COVID-19.Results: The results of this investigation shows, unnecessary travel, 3Cs, and touching own body parts should be avoided. Wearing a mask and proper hand washing are important to reduce the spread of coronavirus.Conclusion: The SARS-CoV-2 has affected more than 11 million people around the world. The second spike of COVID-19 is also alarming for people. It is important to follow the instruction provided by the WHO, CDC, and other national and international governing bodies. The AHP method was used to check various measures that are spreading the coronavirus disease. It demonstrated that 3Cs (spaces that are closed, crowded, and involve close contacts) and travel, shaking hand, unnecessary touching own body parts should be avoided.Keywords: pandemic COVID-19, preventive measure, decision making, AHP, SARS-CoV-2